The adjustment bureau - Nolfi, George; Damon, Matt.; Blunt, Emily; Slattery, John, 1963-; Mackie, Anthony, 1979-; Dick, Philip K.; Universal Pictures (Firm); Media Rights Capital (Firm); Universal Studios Home Entertainment (Firm) (Universal City, CA : Universal Studios Home Entertainment, 2011)
A man glimpses the future fate has planned for him and chooses to fight for his own destiny. Battling the powerful Adjustment Bureau across, under, and through the streets of New York, he risks his destined greatness to be with the only woman he's ever loved.
Title from disc surface.
Director of photography, John Toll ; editor, Jay Rabinowitz ; music, Thomas Newman.
Matt Damon, Emily Blunt, John Slattery, Anthony Mackie.
Rating: PG-13; for brief strong language, some sexuality and a violent image.
DVD; anamorphic widescreen (1.85:1) presentation ; Dolby digital 5.1 surround (English, Spanish and French) and DVS 2.0 stereo. surround (English).
English, French or Spanish language tracks; English, French or Spanish subtitles; SDH.
Keywords: Ballerinas -- Drama; Political candidates -- Drama; Man-woman relationships -- Drama; Thrillers (Motion pictures); Science fiction films; Feature films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities